Genetic Analysis of Adult Plant Resistance to Stripe Rust in Common Wheat Cultivar “Pascal” - Bai, Bin; Li, Zimeng; Wang, Hongmei; Du, Xiaolin; Wu, Ling; Du, Jiuyuan; Lan, Caixia (Frontiers in Plant Science, 2022)
Wheat stripe rust is an important leaf disease to affect the wheat yield globally. Breeding resistant wheat varieties is one of the most economically and environmentally effective way to control this disease. The common wheat (Triticum aestivum L.) cultivar ‘Pascal’ exhibited susceptible to stripe rust at the seedling stage but it showed high resistance to stripe rust at the adult plant stage over twenty years in Gansu, a hot spot of the disease in northwestern China. In order to understand the genetic mechanism of stripe rust resistance in this cultivar, 55K SNP array was used to analyze the two parents and the 220 recombinant inbred lines (RILs) derived from the cross of ‘Huixianhong’ × ‘Pascal’. We detected three new stripe rust adult plant resistance (APR) QTL contributed by Pascal, viz. QYr.gaas-1AL, QYr.gaas-3DL and QYr.gaas-5AS, by using inclusive composite interval mapping method. They flanked by SNP markers AX-111218361—AX-110577861, AX-111460455—AX-108798599 and AX-111523523—AX-110028503, respectively, and explained the phenotypic variation from 11.0 to 23.1%. Bulked segregant exome capture sequencing (BSE-seq) was used for fine mapping of QYr.gaas-1AL and selection of candidate genes, TraesCS1A02G313700, TraesCS1A02G313800, and TraesCS1A02G314900 were three strong candidates for QYr.gaas-1AL. KASP markers BSE-1A-12 and HXPA-3D for QYr.gaas-1AL and QYr.gaas-3DL were respectively developed for breeders to breed durable stripe rust resistant wheat varieties.